Stem cells and their potential as cardiac therapeutics (Faculty of Medicine Universitas Indonesia, 2006)
Stem cells are the foundation cells for every organ and tissue in the body. They are undifferentiated cells that under proper conditions begin to develop into specialized tissues and organs. Most of the body's specialized cells cannot be replaced by natural processes if they are seriously damaged or diseased, such as in Myocardial Infarction. Recent interest has focused on stem cells, which can proliferate, and differentiate into cardiomyocytes.This paper aim to provide overview of stem cell transplantation in myocardial infarction, milestones and setbacks in the study of cellular cardiomyoplasty. (Med J Indones 2005; 15:3-8) Keywords: Stem cell, myocardial infarction, cellular cardiomyoplasty